We Must Draw a Different Future! Insights from the Frontline Anti-Violence Work During the Pandemic in Italy - Demurtas, Pietro; Peroni, Caterina (PARTECIPAZIONE E CONFLITTO, 2023)
In this article we analyze the effects of the Covid-19 pandemic on the Italian anti-violence system, through the eyes of the pratictioners of anti-violence centers, who are historically at the forefront in supporting women survivors of male violence. Their perspective is particularly relevant because, in Italy, anti-violence centers hold a "borderline" position, which lies between the political role of transformation and that of an actor of the private social provider of an 'essential' public service. On the basis of international recommendations, our analysis distinguishes two main areas of intervention on which national policies have been called to intervene: on one side, the protection of women victims of violence, and on the other their empowerment. Analyzing either official statistics and data collected through an online survey addressed to the practitioners of anti-violence centers during the lockdown, we highlight strengths and weaknesses of the policy measures implemented in Italy from their situated perspective, with reference both to the protection and the empowerment of survivors.